Minecraft Stonesword Saga : Mobs Rule! - Book 2 - Eliopulos, Nick; Batson, Alan; Hill, Chris 1970- (Chris Costigan) (New York : Random House, 2022)
"Something has turned the Evoker King to stone, and elements of his code have turned into new and terrible bosses that threaten the digital world of Minecraft. Now Po, Harper and their friends must travel deep into underground and into a web of danger to face the one of them. But that's the easy part, because in the real world, Po decides to run for class president and before he knows it, the ground feels like it is opening under his feet and his popularity is about to plummet!"--|cFrom publisher's description.
Keywords: Minecraft (Game) -- Juvenile fiction; Virtual reality -- Juvenile fiction; Computer games -- Juvenile fiction. -- Programming; Video games -- Juvenile fiction; Minecraft (Game) -- Fiction; Virtual reality -- Fiction; Computer games -- Fiction. -- Programming; Video games -- Fiction; Fantasy fiction